2014
DOI: 10.1016/j.acvd.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Real-time three-dimensional foetal echocardiography using a new transabdominal xMATRIX array transducer

Abstract: The new xMATRIX transabdominal transducer allows a multimodality approach to the foetal heart. Further studies that include foetuses with cardiac malformations are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…With the inherent nature of low cost [64] and no radiation, the capacity of dynamically visualizing the anatomy and geometry in real-time and user-friendly interaction with the operators expands the application of real-time 3D US imaging in clinical examinations increasingly. The main approaches to accomplishing a real-time US imaging system are systematically discussed in this review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the inherent nature of low cost [64] and no radiation, the capacity of dynamically visualizing the anatomy and geometry in real-time and user-friendly interaction with the operators expands the application of real-time 3D US imaging in clinical examinations increasingly. The main approaches to accomplishing a real-time US imaging system are systematically discussed in this review.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, real-time 3D US imaging can also be applied to assist the diagnosis in rib anomalies, fluid accumulation, and abnormal spine curvature [63]. Utilizing matrix array transducer allows multimodality, for example, live xPlane imaging and live 3D surface, to examine the fetal heart in real-time [64]. …”
Section: Applicationsmentioning
confidence: 99%
“…Acquired 3D volume data can be displayed in three orthogonal planes and provide all the 2D planes for a complete anatomical evaluation of the particular organ. Therefore, 3D-ultrasound with multiplanar reconstruction or surface rendering has advantages in the evaluation of complex anatomy, such as fetal heart, central nervous system and face [ 6 7 8 9 10 ]. For example, a single volume sweep provides reconstruction of a midsagittal plane for evaluation of nuchal translucency and nasal bone [ 11 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of 3D and 4D ultrasound probes in 2003 by General Electric and Philips Ultrasound, a new era of fetal cardiovascular imaging was introduced as research concepts evolved into clinical tools . The Philips xMATRIX array probe was designed for applications in adult and pediatric cardiology, but did not gain wide range utilization in the obstetrical community as supported by the paucity of publications describing its use in fetal cardiology . The probe introduced by GE ultrasound was a 3D/4D probe using a mechanical sweep technique called spatial‐temporal image correlation (STIC) in which multiple 2‐dimensional images were stacked one behind the other to create a volume dataset .…”
Section: Introductionmentioning
confidence: 99%
“…From the STIC acquisition, three‐dimensional voxels were created that had an X, Y, and Z component, resulting in three simultaneously displayed images referred to as the A, B, and C planes (Figure ). Following the first publication describing the STIC technique, numerous studies have been reported describing the use of this technique for evaluation of fetal cardiovascular structures and function …”
Section: Introductionmentioning
confidence: 99%